2017
DOI: 10.1021/jacs.7b00154
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Methylated Cytosine Flipping by UHRF1

Abstract: DNA methylation patterns, which are critical for gene expression, are replicated by DNA methyltransferase 1 (DNMT1) and ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) proteins. This replication is initiated by the recognition of hemimethylated CpG sites and further flipping of methylated cytosines (mC) by the Set and Ring Associated (SRA) domain of UHRF1. Although crystallography has shed light on the mechanism of mC flipping by SRA, tools are required to monitor in real time how SRA reads DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 67 publications
(159 reference statements)
12
58
0
2
Order By: Relevance
“…To experimentally evidence that UM63 targets the 5mC binding pocket on SRA, we replaced the wild‐type SRA with a SRA‐G448D mutant where the glycine 448 residue is replaced by a more bulky aspartic acid to block the binding pocket and prevent base flipping . As expected, only marginal binding was observed with this mutant (Figure B), confirming that the 5mC binding pocket of SRA is the target of UM63, in line with molecular modeling predictions.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…To experimentally evidence that UM63 targets the 5mC binding pocket on SRA, we replaced the wild‐type SRA with a SRA‐G448D mutant where the glycine 448 residue is replaced by a more bulky aspartic acid to block the binding pocket and prevent base flipping . As expected, only marginal binding was observed with this mutant (Figure B), confirming that the 5mC binding pocket of SRA is the target of UM63, in line with molecular modeling predictions.…”
Section: Resultssupporting
confidence: 79%
“…As expected, only marginal binding was observed with this mutant (Figure B), confirming that the 5mC binding pocket of SRA is the target of UM63, in line with molecular modeling predictions. To further explore the base‐flipping inhibition by UM63, we investigated by the stopped‐flow technique how UM63 alters the kinetics of the SRA‐induced 5mC flipping in the th G‐labeled DNA . In line with our previous study, the kinetic trace of the th G‐labeled DNA in the presence of SRA showed a slow component with a rate constant of approximately 6.5 s −1 attributed to the 5mC base‐flipping process (Figure , red curve).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Dans ce contexte, l'objectif de notre travail publié dans la revue J Am Chem Soc, a été de suivre et de caractériser la dynamique du basculement des cytosines méthylées sous l'effet du domaine SRA de la protéine UHRF1 qui reconnaît l'ADN hémi-méthylé [6]. Pour atteindre cet objectif, nous avons utilisé deux analogues fluorescents de nucléosides très innovants, la 2-thiényl-3-hydroxychromone (3HCnt) capable de substituer toutes les nucléobases de l'ADN [7] et la thiénoguanosine (thG) qui remplace parfaitement la guanine [8,9].…”
Section: Dnmt1unclassified
“…Par ailleurs, nous avons véri-fié que (1) les analogues thG et 3HCnt n'affectent pas ou peu la stabilité du double brin d'ADN dans lequel ils sont insérés, et (2) qu'aux positions où ces sondes sont sensibles au basculement de base induit par SRA, ce domaine conserve une affinité préférentielle pour les séquences hémi-méthylées par rapport aux séquences non méthylées. Ces sondes ont permis également de déter-miner par une technique de « stoppedflow 1 » que la liaison du domaine SRA avec l'ADN est rapide et donc compatible avec l'activité de lecture de l'UHRF1 pour trouver les sites à méthyler sur le brin d'ADN néo-synthétisé [6,11]. En revanche, l'interaction de SRA avec la cytosine méthylée et le bascu-…”
Section: Dnmt1unclassified